AB0137 Alterations in microrna expression profiles in primary sjÖgren's syndrome and systemic lupus erythematosus. (15th June 2017) - Papp, G; Chen, J-Q; Pόliska, S; Szabό, K; Tarr, T; Bálint, BL; Szodoray, P; Zeher, M
Abstract : Background: MicroRNAs (miRNAs) are single-stranded, endogenous non-coding small RNAs, ranging from 18 to 25 nucleotides in length. MiRNAs are essential in regulating gene expression, cell development, differentiation and function. Dysregulation in miRNAs expression may contribute to the development of autoimmunity. However, a given miRNA may have hundreds of different mRNA targets and a target might be regulated by multiple miRNAs, thus the characterisation of dysregulated miRNA expression profiles could give a better insight into the development of immunological disturbances in autoimmune diseases. Objectives: The aim of our study was to examine the changes in miRNA expression profiles in patients with primary Sjögren's syndrome (pSS) and systemic lupus erythematosus (SLE). Methods: Eight pSS patients, 8 SLE patients and 7 healthy control subjects were enrolled in the investigation. MiRNAs were isolated from peripheral blood mononuclear cells, and expression patterns were determined with Illumina next-generation sequencing technology. Since the immunopathogenesis of pSS and SLE encompasses pronounced B cell hyperactivity along with specific autoantibody production, we paid a special attention on the association between miRNA expression levels and altered peripheral B cell distribution. Results: In SLE patients 135, while in pSS patients 26 miRNAs showed altered expression. Interestingly, the 25 miRNAs including miR-146a, miR-16 and miR-21, which were over-expressed in pSS patients, were found to be elevated in SLE group, as well. On the contrary, we observed the down-regulation of miR-150–5p, which is a novel and unique finding in pSS. Levels of several miRNAs over-expressed in SLE, were not changed in pSS, such as miR-148a-3p, miR-152, miR-155, miR-223, miR-224, miR-326 and miR-342. Expression levels of miR-223–5p, miR-150–5p, miR-155–5p and miR-342–3p, which miRNAs are potentially linked to B cell functions, showed associations with the B cell proportions within peripheral blood mononuclear cells. Conclusions: The observed differences in miRNA expression profiles and the better understanding of immune regulatory mechanisms of miRNAs may help to elucidate the pathogenesis of pSS and SLE. Acknowledgements: This work was supported by the ÚNKP-16–4-III New National Excellence Program of the Ministry of Human Capacities. Disclosure of Interest: None declared